THE ROLE OF LANGUAGE IN SHAPING TEACHERS’ IDENTITY ON TIKTOK - Kadek Dwi Candra Oktariana; I Gede Budasi; Dewa Putu Ramendra (Universitas PGRI Palembang, 2024)
TikTok application is one of the most used applications recently. From 14 years old until 30 years old people spend more than 30 minutes a day opening this application. Enormous, interesting videos with varied topics make many people like TikTok. Besides that, they can create their video easily with the features which are already provided. This phenomenon affects education as well. Teachers try to utilize this application as their learning media. Not only that, but teachers also create their accounts and upload videos that are related to the learning process or education. Therefore, the researcher is interested to know how the language used by teachers in TikTok shapes their identity. The researcher analyzed two subjects, two of them teachers in different countries. This research used a qualitative method that describes the language used in three videos in teachers’ TikTok accounts and analyses it. The findings revealed that both teachers wanted to be seen as capable and friendly teachers because they know how to build an interesting learning process and build good relationships with their students.